Economic, environmental, and social dimensions of farming sustainability – trade-off or synergy? - Grzelak, Aleksander; Borychowski, Michał; Staniszewski, Jakub (Technological and Economic Development of Economy, 2022)
Prior studies on the relationships between economic, environmental, and social dimensions of activity on agricultural holdings has yielded inconclusive results. This study examines the interactions between these spheres, with the aim of determining what the relationships between them might be. The study was based on the results of surveys of 120 farms in the Wielkopolska region of Poland, using structural equation modeling. The results showed significant and positive relationships between the economic, social, and environmental dimensions that could create synergies between them. The strongest positive relationships existed between the economic and environmental dimensions. Thus, economic and environmental development can be stimulated simultaneously. Analyzed farms from the Wielkopolska region positively discount the existing support system in the EU to the complementarity between environmental and economic governance. Our research indicates the need for the EU to implement a strategy adjusted to the individual region’s peculiarities in terms of environmental and social policies in rural areas.First published online 04 March 2022